Social media use in justice administration : disintermediation, conversation and collaboration - Ure, Mariano (2019)
Fil: Ure, Mariano. Pontificia Universidad Católica Argentina. Observatorio de Medios UCA. Programa de Estudios en Comunicación, Medios y Tecnologías; Argentina